ASSOCIATION OF BIOMOLECULES OF SECRETORY ACTIVITY OF VISCERAL ADIPOCYTES WITH ELECTROPHYSIOLOGICAL SIGNS OF METABOLIC DISORDERS OF MYOCARDIUM IN CORONARY ATHEROSCLEROSIS AND METABOLIC SYNDROME - Yu. I. Ragino; N. A. Timoshenko; A. M. Chernjavskyi; S. Yu. Tcimbal; V. S. Shramko; E. V. Kashtanova (Российский кардиологический журнал)
Aim. Assessment in the blood of coronary atherosclerosis (CA) patients with metabolic syndrome (MS), of biomarkers associated with secretory activity of visceral adipocytes, and search for their associations with electrophysiological signs of metabolic cardiomyopathy (MCP).Material and methods. Totally, 123 males included, age 41-79 y. o., with CA verified by coronary arteriography, and with stable angina. ECG recording completed at rest in 12 standard leads with Minessota coding. On ECG, the markers of MCP were analyzed: QT interval duration, corrected QT, ST shift above isoline >0,5 mm, ST depression below isoline >0,5 mm of non-ischemic type, T-wave changes, syndrome TV1>TV6, signs of the left ventricle hypertrophy (LVH), disorders of rhythm and conduction. The components and signs of MC were analyzed: waist circumference, arterial pressure, levels of lipids and glucose in blood. In the blood, by immune enzyme method, the following markers were measured: tumor necrosis factor alpha (TNF-alpha), interleukin 6 (IL-6), leptin, resistin, adiponectin, C-reactive protein.Results. Metabolic syndrome in general was found in 86 men (69,9%) with abdominal obesity and CA. Level of TNF-alpha was increased in 47,2% males, IL-6 level — in 72,4%, hsCRBP — in 64,2%, leptin — in 47%, resistin — in 54%, adiponectin was decreased in 22% cases. In MS males resistin concentration was 1,6 times higher. In subgroup of the persons with ECG signs of LVH 76,5% of males had MS, and adiponectin was lower 1,3 times comparing to non-LVH subgroup. Level of TNF-alpha in males with elevated ST was 1,77 times higher than in those non-ST-elevation. In subgroup of males with TV1>TV6 syndrome the level of resistin was higher 1,4 times comparing to those with no TV1>TV6 syndrome. In subgroup of T-wave changes 83% males had MS, and resistin level was 1,3 times higher comparing to those with no T wave changes. In subgroup of ECG signs of rhythm and conduction disorder in 78,7% of males there was MS, and levels of IL-6 and leptin were 1,6 and 1,9 times higher, respectively, comparing to those with no arrhythmias. In multifactorial regression analysis the following positive associations were found (pTV6 syndrome with resistin level (OR =1,172); T wave variability with resistin (OR =1,101).Conclusion. The results reflect the influence of metabolic changes in the body, associated with secretory activity of visceral adipocytes, on the onset and development of not just MS, but MCP.